The ancient civilizations' conflict in North Africa during the first millennium BCE - Milad, Hussein Ali Khalifa (Al-Mukhtar Journal of Social Sciences, 2024)
This paper addresses the topic of military conflicts among colonial powers that alternated in controlling North Africa during the first millennium BCE. The study includes the conflict between the Carthaginian Empire, which asserted dominance over all Phoenician settlements in the region, and the Greek Empire that sought to extend its influence in the western part of the Triarchy region (Cyrenaica – Barka – Leptis). The study will also delve into the political and military conflicts between Carthage and the Roman Empire in Sicily and North Africa. It adopts a rigorous approach to analyze the historical context and the cultural and political impacts of these conflicts on the development of the region.
Keywords: North Africa; Conflict; Carthage; Greeks; Romans